A Two-Year Longitudinal Study of Emotionally Focused Therapy for Couples: Maintenance and Predictors of Relationship Change - Wiebe, Stephanie (Université d'Ottawa / University of Ottawa, 2014)
Emotionally Focused Therapy for Couples (EFT) is an evidence-based couple therapy with excellent outcomes (Johnson, Hunsley, Greenberg & Schindler, 1999) and strong results in follow-up (Cloutier, Manion, Walker & Johnson, 2002). Although EFT strives to create lasting change for couples through the creation of secure attachment bonds, research has had yet to clarify how couples maintain changes across time. According to EFT, relationship satisfaction improvements are associated with and arise from the creation of secure attachment bonds that allow couples to turn to each other in times of stress, fostering resilience in the relationship across time (Johnson & Whiffen, 1999). One goal of this study was to test this assumption by modeling the trajectory of how relationship satisfaction and self-reported and behaviourally measured attachment security progress during the course of two years after finishing therapy. The trajectory of relationship satisfaction, and relationship specific self-reported and behaviourally measured attachment were modeled across pre-therapy, post-therapy and 6, 12, 18 and 24 months follow-up in a sample of 32 couples who received an average of 21 sessions of EFT. Results demonstrated a significant growth pattern using Hierarchical Linear Modeling (HLM: Raudenbush & Bryk, 2002) demonstrating increases in relationship satisfaction and secure base behaviour, and decreases in attachment anxiety from pre to post therapy that levelled off during the follow-up period. Although these results demonstrated strong EFT outcomes across follow-up, there was variability in outcomes. A second goal of this study was to investigate predictors of relationship satisfaction across follow-up. Results indicated that decreases in relationship specific attachment anxiety and avoidance, and increases in trust as well as depth of experiencing during therapy predicted higher relationship satisfaction across follow-up.